Renal Mucinous Tubular and Spindle Cell Carcinoma A Case Report - Hamada, Kazuki (Hinyokika kiyo. Acta urologica Japonica, 2021)
Renal mucinous tubular and spindle cell carcinoma (MTSCC) is a rare kidney cancer subtype with limited cases reported in the literature. Renal MTSCC has many similarities with papillary renal cell carcinoma (pRCC), and it is therefore often difficult to make a differential diagnosis between them. Herein, we report a case of renal MTSCC. The patient was a 76-year-old woman. Computed tomography revealed a left renal tumor. Magnetic resonance imaging (MRI) demonstrated an iso-intensity or high signal intensity mass on T2-weighted images, high signal intensity on diffusion-weighted images, and weak and gradual enhancement. We diagnosed the patient with left renal cell carcinoma (cT1bN0M0) and performed laparoscopic left nephrectomy in May 2019. The histopathological diagnosis was renal MTSCC. Six months after surgery, the patient remains free of recurrence and of metastasis. MRI is effective for the preoperative differentiation of renal MTSCC from pRCC since renal MTSCC presents an iso-intensity or high signal intensity on MRI T2-weighted images reflecting the mucin component in the intervening stroma within the tumor